ANALISIS MAKNA IDIOM KI NI NARU, KI NI KAKARU, KI NI KAKERU DAN KI NI SURU MENGGUNAKAN IDIOM CONTROL TABLE - Efendi, Abdul Muhar; Widiati, Sri Wahyu; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is about idiom ki ni naru, ki ni kakaru, ki ni kakeru, and ki ni suru. The purpose of this research is to find the classification of these four idioms based on term and appropriate with used method. This research is qualitative descriptive research, cause describe of these four idioms with using words and analys and the datas be in form sentence from corpus of data. Analysis method uses theory advanced by Masahiro Oku (1992) in his journal “Methods for Analyzing Japanese Predicate Idioms and Function Verb Expresions”. The instrument is idiom control table in the form of schema and table as a guide to processing these four idioms with three terms. Result of this research is these four idioms just complete the third term. That term is meaning from one of idiom forming elements can be affected by other words beside the forming elements.Keywords: Idiom, ki ni naru, ki ni kakaru, ki ni kakeru, ki ni suru.